Question
upstudy study bank question image url

\[ \left\{\begin{array}{c}2 x+2 y=-12 \\ x-2 y=6\end{array}\right. \] Determine if the point \( (2,-2) \) lies on both of the lines in the system of equations by substituting the ordefed pair into both equations.

Ask by Murphy Reed. in the United States
Feb 03,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

The point \( (2, -2) \) does not lie on both lines in the system of equations.

Solution

Evaluate the expression by following steps: - step0: Evaluate: \(2x+2y\) - step1: Substitute: \(2\times 2+2\left(-2\right)\) - step2: Multiply the numbers: \(4+2\left(-2\right)\) - step3: Multiply the numbers: \(4-4\) - step4: Subtract the numbers: \(0\) Substitute \( x=2,y=-2 \) into the expression \( x - 2y \). Evaluate the expression by following steps: - step0: Evaluate: \(x-2y\) - step1: Substitute: \(2-2\left(-2\right)\) - step2: Multiply the numbers: \(2+4\) - step3: Add the numbers: \(6\) To determine if the point \( (2, -2) \) lies on both lines represented by the equations in the system, we will substitute \( x = 2 \) and \( y = -2 \) into each equation. 1. **First Equation:** \[ 2x + 2y = -12 \] Substituting \( x = 2 \) and \( y = -2 \): \[ 2(2) + 2(-2) = 4 - 4 = 0 \] The left side equals \( 0 \), which does not equal \( -12 \). Therefore, the point does not satisfy the first equation. 2. **Second Equation:** \[ x - 2y = 6 \] Substituting \( x = 2 \) and \( y = -2 \): \[ 2 - 2(-2) = 2 + 4 = 6 \] The left side equals \( 6 \), which matches the right side. Therefore, the point satisfies the second equation. ### Conclusion: The point \( (2, -2) \) does not lie on the first line but does lie on the second line. Thus, it does not lie on both lines in the system of equations.

Reviewed and approved by the UpStudy tutoring team

error msg
Explain
Simplify this solution

Extra Insights

To determine if the point \( (2, -2) \) lies on both lines represented by the equations in the system, we need to substitute \( x = 2 \) and \( y = -2 \) into both equations. For the first equation \( 2x + 2y = -12 \): \[ 2(2) + 2(-2) = 4 - 4 = 0 \neq -12 \] For the second equation \( x - 2y = 6 \): \[ 2 - 2(-2) = 2 + 4 = 6 \] The point \( (2, -2) \) satisfies the second equation but not the first one. Therefore, it does not lie on both lines. Alternatively, you could graph the equations to visually confirm the intersection or lack thereof. Graphing them can reveal how they meet (or don't) in the coordinate plane, turning numbers into a picture—sometimes, that's how you can more easily see relationships!

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy